The impact of management on the behavior of an isolated logistics population - Колянова, Тетяна Володимирівна (Київський національний університет імені Тараса Шевченка, 2021)
The article considers the isolated population described by the logistic equation and studies the influence of management on the change of its number. Depending on the value of the control parameter, there are three different cases of behavior of an isolated population. In the first case, when the quota is equal to the corresponding value, depending on the initial value, the population either goes to a stationary value, or dies out. In the second case, when the quota does not exceed the established value, depending on the initial population size, the population either goes to the largest stationary point, or dies out. And in the third case, when the quota exceeds the established value, regardless of the initial population size, the population dies out. Stationary points for stability in all three cases are studied and graphs of population behavior depending on different initial conditions are presented. Pages of the article in the issue: 81 - 84 Language of the article: Ukrainian
Keywords: logistic population; differential equation; stationary point; stability; management; логістична популяція; диференціальне рівняння; стаціонарна точка; стійкість; керування